How do in-store environmental cues influence Malaysian shoppers? A study of hypermarket customers in Malaysia - Wee, Y.G.; Ahmad, K.Z. (2010)
The importance of retail store design and merchandising policies rests in the ability of the physical retail environment to alter shopping reactions and behaviour. Specifically, this research paper examines relationship between physical hypermarket environments, Malaysian shoppers’ emotions and their subsequent shopping behaviour besides considering the role of self regulation as moderator of relationships between consumers’ shopping emotions and their post shopping evaluations. Overall, the findings of this study refute the general postulation that shopping emotions directly influence resource expenditure and shopping values. Results also contradict with previous research which indicates that action oriented shoppers are less responsive to environmental stimuli and subsequently spend less on resource expenditure because puzzled findings from this study reflects that Malaysian shoppers spend more money than they expect despite having high self degree of control.Significantly, findings show that feelings of dominance, previously dismissed as unimportant, significantly alter the shopping behavior of Malaysian shoppers. Therefore, this study proves the relevancy of measuring ‘dominance’ in the shopping emotions analysis. And finally, the last test result of this study postulates the rise of hedonic values experienced by Malaysian shoppers resulted from increased resource expenditures.